A before–after control–impact assessment to understand the potential impacts of highway construction noise and activity on an endangered songbird. Issue 1 (20th December 2016) - Long, Ashley M.; Colón, Melanie R.; Bosman, Jessica L.; Robinson, Dianne H.; Pruett, Hannah L.; McFarland, Tiffany M.; Mathewson, Heather A.; Szewczak, Joseph M.; Newnam, J. Cal; Morrison, Michael L.
Abstract: Anthropogenic noise associated with highway construction and operation can have individual‐ and population‐level consequences for wildlife (e.g., reduced densities, decreased reproductive success, behavioral changes). We used a before–after control–impact study design to examine the potential impacts of highway construction and traffic noise on endangered golden‐cheeked warblers ( Setophaga chrysoparia ; hereafter warbler) in urban Texas. We mapped and monitored warbler territories before (2009–2011), during (2012–2013), and after (2014) highway construction at three study sites: a treatment site exposed to highway construction and traffic noise, a control site exposed only to traffic noise, and a second control site exposed to neither highway construction or traffic noise. We measured noise levels at varying distances from the highway at sites exposed to construction and traffic noise. We examined how highway construction and traffic noise influenced warbler territory density, territory placement, productivity, and song characteristics. In addition, we conducted a playback experiment within study sites to evaluate acute behavioral responses to highway construction noises. Noise decreased with increasing distance from the highways. However, noise did not differ between the construction and traffic noise sites or across time. Warbler territory density increased over time at all study sites, and we found no differences in warbler territory placement, productivity, behavior, or song characteristics that we can attribute to highway construction or traffic noise. As such, we found no evidence to suggest that highway construction or traffic noise had a negative effect on warblers during our study. Because human population growth will require recurring improvements to transportation infrastructure, understanding wildlife responses to anthropogenic noise associated with the construction and operation of roads is essential for effective management and recovery of prioritized species. Abstract : We used a before–after control–impact study design to examine the potential impacts of highway construction and traffic noise on endangered golden‐cheeked warblers ( Setophaga chrysoparia ; hereafter warbler) in urban Texas. Noise decreased with increasing distance from the highways. However, we found no evidence that noise differed between construction and traffic noise sites or across time. Warbler territory density increased over time at all study sites, and we found no differences in warbler territory placement, productivity, behavior, or song characteristics that we can attribute to highway construction or traffic noise. Photo credit: Jill Wussow.